Análise da diversidade microbiana aquática em rios e lagos da região amazônica - Toyama, Danyelle (Universidade Federal de São Carlos, 2012)
The Amazon region has the largest hydrographic basin on the planet, the one that includes Amazon River, and it also has the largest rainforest in the world. Moreover, it presents a great biological diversity, both related to the fauna and flora, and microbiological. Microorganisms are responsible for most biogeochemical cycles that shape the terrestrial environment and the freshwater and marine ecosystems, and they can be widely exploited biotechnologically. It is estimated that less than 1% of all bacterial species is known due to our inability to simulate the environment in which they live. However, new techniques have allowed the study of these microorganisms. Through Metagenomics it is possible to study complex environmental samples without the need for isolation and individual cultivation of these organisms. For this purpose, the16S ribosomal DNA (16S rDNA) is used in bacteria and archaea in order to study phylogeny and diversity. This sequence is used because it has been fairly maintained during the processes of biological evolution and it may serve as an indicator of how organisms are closely related. For these studies, this region was amplified by the Polymerase Chain Reaction (PCR) and cloned into vectors through the recombinant DNA technology, thus enabling the construction of 16S rRNA libraries. These libraries were then sequenced and the microorganisms were identified by comparison with databases. In this study it was used DNA extracted from Solimões River filtered water, in addition to water from other rivers and adjacent lakes, to the construction of libraries, in order to study the biodiversity through 16S rRNA analysis. In all libraries, phylum Proteobacteria was the most abundant, and most of the genera observed belong to the Betaproteobacteria class. The freshwater cosmopolitan taxa Candidatus Planktophila limnetica and Polynucleobacter were observed, as well as primary producers were represented by the genera Synechococcus and Cyanobium. Samples in which the construction of 16S rRNA libraries was possible for Archaea, the phylum Crenarchaeota was the most abundant in all libraries.
Keywords: Genética; Actinobacteria; Amazônia; Betaproteobacteria; Crenarchaeota; Polynucleobacter; Rio Solimões; Actinobacteria; Amazonia; Betaproteobacteria; Crenarchaeota; Polynucleobacter; Solimões River; CIENCIAS BIOLOGICAS::GENETICA